Overview of Third Trimester Pregnant Women's Urine Leukocyte Sediment and Protein Levels at the Laboratory of Anggrek Mas Hospital, West Jakarta - Halimah Nurul Istiqomah; Septiani; Muhammad Rizki Kurniawan; Dian Rachma Wijayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Pregnant women with the third trimester of pregnancy (7-9 months or 29-40 weeks), most of them give birth normally, but 15% of cases are life-threatening complications, namely preeclampsia. Preeclampsia is characterized by increased proteinuria. Women during pregnancy are more at risk of suffering from urinary tract infections because of the physiological changes that occur in their bodies. As many as 20% of cases of urinary tract infection occur in pregnant women. Examination of urine protein and urine leukocyte sediment in pregnant women is very important as a support for the risk of preeclampsia and urinary tract infections. This study used descriptive analysis with a cross-sectional design, namely one-time observation. Data used by third trimester pregnant women. The research was conducted in January-July 2022 at the Anggrek Mas Hospital Clinical Laboratory. There are 20 research subjects. With the highest protein levels at high risk of preeclampsia were (+3) 1 pregnant woman and (+4) 3 pregnant women. Then the leukocytes of the urine sediment are above normal values≥5/Landang Besar, namely there are 12 pregnant women each. In the majority of third trimester pregnant women at Anggrek Mas Hospital, West Jakarta, all pregnant women who were observed, the results of urine protein levels were found to be abnormal and urine sediment leukocytes were found to be above normal values